Prevalence and risk factors for tobacco, khat, and alcohol consumption among high school students in Ethiopia - Selamawit Hirpa; Andrew W Fogarty; Adamu Addissie; Linda Bauld; Thomas Frese; Susanne Unverzagt; Eva J. Kantelhardt; Sefonias Getachew; Wakgari Deressa (BMC, 2023)
Abstract Background Tobacco, khat, alcohol, and marijuana are the main risk factors for non-communicable diseases. There are limited studies on substance use in Ethiopia, especially among secondary school students. This study aims to determine the epidemiology of substance use among secondary school students in Ethiopia. Methods This cross-sectional study was conducted in March 2020 in four large regions of Ethiopia and the capital Addis Ababa. We collected data from 3,355 grade 9 and grade 10 students in 36 randomly selected high schools. Data were collected on tobacco, khat, alcohol and other substances. Mixed effect logistic regression models were fitted to determine the predictors of cigarette smoking. Results 157 (4.7%) of the participants ever smoked cigarettes and 81 (2.4%) were current smokers. 106 (3.2%) ever used smokeless tobacco, 1,342 (41.8%) had ever drunk alcohol, 290 (8.7%) ever used khat, 137 (4.8%) chewed khat regularly and 76 (2.3%) ever used marijuana. There was a significant regional variation in substance use patterns; cigarette and khat use was the highest in southern regions, whereas alcohol use was highest in the northern areas. Availability of cigarette and khat shops within a 100-meter radius of the school compound was reported by 1,229 (37.5%) and 816 (25%) students, respectively. Three hundred fifty-four (10.9%) students had ever seen someone smoking a cigarette in the school compound. Ever use of smokeless tobacco (Adjusted Odds Ratio (AOR) = 9.4, 95%CI: 4.9-17.9), ever use of shisha (AOR = 8, 95% CI: 3.9-16.3), ever use of khat (AOR = 4.1, 95%CI: 2.5-6.8), ever use of alcohol (AOR = 2.3, 95%CI: 1.4-3.7), having a friend who smoked a cigarette (AOR = 2, 95%CI: 1.2-3.5), and ever seen someone smoking a cigarette in the school compound (AOR = 1.9, 95%CI: 1.1-3.4) were associated with ever use of cigarettes. Conclusion Substance use prevalence in Ethiopia has regional variations and prevention strategies should be tailored to the needs of the regions. Although this study reported a lower prevalence of cigarette smoking, students could access cigarettes and khat in nearby school areas. The existing tobacco control laws that prohibit selling tobacco products to children and adolescents under 21 years of age and ban establishing tobacco shops close to school compounds should be enforced.